Licitações sustentáveis instrumento legal de promoção da sustentabilidade: um estudo da aquisição de bens na Universidade Federal do Espírito Santo - UFES - Cypreste, Aline Silva Tavares (2013)
The following paper has as its objective the study of the evolution in the adoption of the sustainable bidding proceeding, making it obligatory in Brazilian federal government procurement through the law nº 12.349/2010. Conceived as an instrument for the promotion of sustainable development it aims to identify its state of operationalization for the acquisition of property in the scope of the Federal University of Espírito Santo – UFES, detecting the barriers, as well as promoting suggestions for the amplification and bettering of this practice. The concern with the social environmental impact of public purchases is already an international reality, for some decades, and recently has shown itself in an expressive form in Brazil that, for this reason, adopted this new model of public purchases. The implementation of sustainable biddings doesn’t constitute discretionary act, but a constitutional and legal imposition that demands the search for the most advantageous proposal, that meets the public interest and contributes to the promotion of sustainable development. The sustainable development is a global challenge and the Brazilian public administration has a key role in the diffusion of public policies of social environmental responsibility and in the incentive to the production and consumption of sustainable goods and services. Although there already are norms on the matter in Brazil, the federal government, however, has yet to regulate more precisely its application so that the sustainable biddings constitute a rule and not the exception in the federal branches. The research utilized a qualitative approach that, in regards to its nature, can be classified as descriptive, assuming the form of exploratory research. The instruments used for the data collection correspond to bibliographical research, documental analysis, unstructured interviews, questionnaires and direct observations. The analysis of the case study of UFES shows the incipiency of the application of sustainable public purchases with relation to the quantity of procedures performed, however, increasing and expressive in terms of expenditure values, that evidentiate the necessity of implementing changes to institutionalize the practice of sustainable public purchases in the university